Analysis of Handling Problems on The Import Process for Performance Improvement (Case Study PT. Kumaitu Cargo) - Komala, Aziza Leila; Julianto, Mohamad Dwi; Firdaus, Aji Matarrusdi; Fariqh, Redy Patrialis Ibnu (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research is motivated by problems that include Import Process / Documentation Errors, Delivery Delays, Miscommunication and Employee Attitudes. The purpose of this study is to analyze how to handle problems in the import process for performance improvement at PT Kumaitu Cargo, to analyze what obstacles PT Kumaitu Cargo faces in improving performance through handling problems in the import process, to analyze what efforts PT Kumaitu Cargo makes to improve performance through handling problems in the import process. This research uses a qualitative method with a descriptive approach, the research location is at PT Kumaitu Cargo, North Jakarta. This research data collection technique is by observation, interview and documentation. The results showed that PT Kumaitu Cargo has successfully handled problems in the import process by utilizing technology. Efforts made by PT Kumaitu Cargo to overcome these obstacles include replacing manual systems with automation to speed up the process and increase efficiency. HR development with continuous training, so that employees can adapt to new technologies and improve the quality of import processes. In addition, the company strives to improve efficiency by speeding up the clearance process at the port, improving worker professionalism, and utilizing technology to optimize the tracking of goods and ensure timely delivery.